Carrot Yoghurt : Sensory, Chemical, Microbiological Properties and Consumer Acceptance - Aly, Salwa A.; Galal, E.A.; Elewa, Neimat A. (Pakistan Journal of Nutrition, 2004)
Plain and carrot yoghurt were prepared in the laboratory scale production from cow`s milk obtained from Fayoum district, Egypt. Carrot yoghurt was prepared by blending milk with 5, 10, 15 and 20% carrot juice before fermentation. The sensory, rheological, chemical, and microbiological quality of yoghurt samples were investigated during refrigerated storage at 4°C for three weeks. The Sensory scores increased especially for yoghurt samples with 15% carrot juice. Chemical analysis revealed an increase in acidity, decrease soluble nitrogen /total nitrogen ratio and curd tension with increasing carrot juice. On the other hand, high carrot juice suppressed the growth of mold and yeast, Coliform organisms while Lactobacillus bulgaricus and Streptococcus thermophillus were not significantly (P > 0.05) affected. Yoghurt with 5, 10, 15 and 20% carrot juice showed a significant decrease (P < 0.05) in aflatoxin M1 respectively. The results of the study showed that carrot had significant effect on the acceptability of yoghurt during shelf life. The economic and public health importance of carrot in yoghurt was discussed.